(untitled) (Leviathan (São Paulo), 2012)
Exploitation and oppression remain key concepts in Erik Olin Wright's social theory, and this piece provides a general mapping of those concepts. These concepts are defined and their connection is cleared out. Marx's theory of industrial reserve army is discussed to make the point that non-exploited workers are potentially useful for understanding how apparently superfluous people for exploiters have an impact on exploitation dynamics. Marx's point contributes to Wright's overall conceptual enterprise